Estimating private financial return on investment in education in Tangail City: A Mincerian Model analysis - Kazi Tabassum; Muhammad Rabiul Islam Liton (Economic Review: Journal of Economics and Business, 2023)
Several reasons are responsible for income disparity across different nations. Education established itself to be the primary reason for such disparities. Therefore, estimation of return on investments in education has become a great concern of the researchers in recent years. In most of the cases researchers used earnings function for estimating return on investments in education and found lower return for developing and least developed countries. Therefore, the study aimed to investigate the private financial return on investments in education in Tangail City of Bangladesh. To pursue the study, the required data from 100 respondents from the study area were collected. The study employed the Mincerian Model for estimating the rate of private financial return on investments in 1 year education in Tangail City. It found the rate 2.1% which is very low. Parallely, the study also revealed that besides education, type of occupation and job experience had a great influence on the income of people of Tangail City.
Keywords: I21; 330; Private Financial Return; Education; Mincerian Model; Tangail